Post-cardiac surgery thrombotic thrombocytopenic purpura: presence of anti-ADAMTS13 autoantibodies at preoperative baseline - Bryan Tordon; Theodore E. Warkentin; Jane C. Moore; Donald M. Arnold (Platelets, 2022)
Thrombotic thrombocytopenic purpura (TTP) rarely complicates acute inflammatory conditions such as surgery, including post-cardiac surgery. Review of 32 previously-reported cases of post-cardiac surgery TTP indicates that this disorder often occurs as early as 2–3 days following surgery, which seems too soon to implicate new formation of anti-ADAMTS13 autoantibodies as a consequence of surgery itself. We diagnosed post-cardiac surgery TTP in a 60-year-old female that began approximately 3 days post-coronary artery bypass surgery in which anti-ADAMTS13 autoantibodies were implicated. We therefore investigated whether anti-ADAMTS13 autoantibodies were also present in a preoperative blood sample. Inhibitory (neutralizing) anti-ADAMTS13 autoantibodies were detectable in the preoperative blood sample, suggesting that the role of surgery in precipitating TTP might be due to effects such as abrupt increase in postoperative von Willebrand factor levels and associated proinflammatory factors, rather than effects of surgery itself leading to the formation of de novo anti-ADAMTS13 autoantibodies.